Extracellular vesicles from mesenchymal stem cells reduce neuroinflammation in hippocampus and restore cognitive function in hyperammonemic rats - Paula Izquierdo-Altarejos; Andrea Cabrera-Pastor; Mar Martínez-García; Carlos Sánchez-Huertas; Alberto Hernández; Victoria Moreno-Manzano; Vicente Felipo (Journal of Neuroinflammation, 2023)
Abstract Chronic hyperammonemia, a main contributor to hepatic encephalopathy (HE), leads to neuroinflammation which alters neurotransmission leading to cognitive impairment. There are no specific treatments for the neurological alterations in HE. Extracellular vesicles (EVs) from mesenchymal stem cells (MSCs) reduce neuroinflammation in some pathological conditions. The aims were to assess if treatment of hyperammonemic rats with EVs from MSCs restores cognitive function and analyze the underlying mechanisms. EVs injected in vivo reach the hippocampus and restore performance of hyperammonemic rats in object location, object recognition, short-term memory in the Y-maze and reference memory in the radial maze. Hyperammonemic rats show reduced TGFβ levels and membrane expression of TGFβ receptors in hippocampus. This leads to microglia activation and reduced Smad7–IkB pathway, which induces NF-κB nuclear translocation in neurons, increasing IL-1β which alters AMPA and NMDA receptors membrane expression, leading to cognitive impairment. These effects are reversed by TGFβ in the EVs from MSCs, which activates TGFβ receptors, reducing microglia activation and NF-κB nuclear translocation in neurons by normalizing the Smad7–IkB pathway. This normalizes IL-1β, AMPA and NMDA receptors membrane expression and, therefore, cognitive function. EVs from MSCs may be useful to improve cognitive function in patients with hyperammonemia and minimal HE.